Desenvolvimento, projeto de construção de um equipamento de reparo de trincas por atrito - Souza, Robson José de (2006)
In the offshore industry, the utilization of conventional process of arc welding processes are frequently used to repair structure defects, such as cracks. These repairs are carried out under water to reduce risks of explosion. Under water welds are subjected to hydrogen embrittlement and severe porosity. An alternative is offered by the friction hydro pillar processing (FHPP), which may be regarded as a process in which a hole is drilled and filled with a consumable rod of the same material. Despite its wide applicability, this technique has not been widely investigated. Motivated by the potentialities of this method, an infrastructure for repairing engineering structures by drilling and filling holes was designed and constructed. The equipment was designed with an axial force capacity of 50 kN, and a tangential force limited to 10 kN. The rotational speed was limited to 8000 rpm. The FHPP parameters were completely automated, where by the user has only to give them. To validate the infrastructure repair tests were carried out in plain carbon steel plats. The obtained results showed that a metallic bond between the substrate and the rod was achieved. The system enables to perform experimental tests in order to optimize the friction hydro pillar process parameters.